+0  
 
0
241
2
avatar

5+3(x-4)=11

Guest May 16, 2017
 #1
avatar
0

https://www.wolframalpha.com/input/?i=5%2B3(x-4)%3D11

Guest May 16, 2017
 #2
avatar+7266 
+1

5 + 3(x - 4) = 11

 

Subtract 5 from both sides of the equation.

3(x - 4) = 6

 

Divide both sides of the equation by 3.

x - 4 = 2

 

Add 4 to both sides of the equation.

x = 6

hectictar  May 16, 2017

23 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.